Should Wellbeing Be a Goal of Schooling? - Schwimmer, Marina (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2023)
Several philosophers and psychologists of education have taken the position that wellbeing should be at the heart of our educational system, if not its primary goal. The aim of this paper is to outline, question, and challenge this position. It starts by discussing the main approaches that consider student wellbeing as the primary goal of the educational system – the propositions of positive psychology and those of certain educational philosophers and psychologists. It follows with an examination of some major social critiques of the idea of wellbeing as a goal of schooling. Drawing mainly on Foucault, the paper questions the extent to which the aim of wellbeing contributes to normalization and hinders the possibility of self-government. The paper concludes that wellbeing should not be conceived as a goal, but rather as an ongoing preoccupation of care for the self.